Druggable targets and therapeutic development for COVID-19 - Duan, Xiaohua; Lacko, Lauretta A.; Chen, Shuibing (Frontiers in Chemistry, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the pathogen causing coronavirus disease 2019 (COVID-19), has led to a worldwide social and economic crisis. Until now, only limited therapeutic regimens have been available for COVID-19 patients, sparking unprecedented efforts to study coronavirus biology. The whole RNA genome of SARS-CoV-2 encodes 29 proteins, including 16 non-structural, 4 structural, and 9 accessory proteins. The viral life cycle includes viral entry into host cells, genome replication and transcription, followed by viral assembly and release. These processes depend on the interactions between viral polypeptides and host proteins, both of which could be potential therapeutic targets for COVID-19. In this review, we discuss the functions of the essential proteins of SARS-CoV-2 and the host factors. We summarize the most updated therapeutic interventions for COVID-19 patients, including those approved clinically or in clinical trials.